Influence of Polyamide-12 composition on the mechanical properties and dimensional accuracy in selective laser sintering - Omar, Mohammad Rafi (2024)
There are significant differences in surface morphology and physical characteristics between the various 3D printed objects that are being produced, which compromises the preciseness of the finished product. This study examines how several key parameters of the Selective Laser Sintering (SLS) 3D printer impact the material strength of Polyamide -12 (PA-12) using the Taguchi optimization method. The primary factorial parameter chosen is the material PA-12, which is a mixture of virgin, heated, and recycled materials. Additional parameters being studied include laser beam strength and layer thickness. Test specimens were fabricated using an SLS 3D printer following normal procedures to evaluate the physical qualities including tensile strength, roughness, impact resistance, and Rockwell hardness, as well as surface morphology and dimensional accuracy. Next, the surface morphology and dimension accuracy of the samples were assessed using a scanning electron microscope (SEM) and coordinate measuring machine (CMM). The optimal results were obtained with 100% virgin PA-12 material with a machine parameter of 60 watts of laser power and a layer thickness of 0.06 mm. This set of parameters achieved the best performance in terms of the mechanical qualities, dimensional accuracy, and part quality. Composition 1, produced completely of virgin material scored the highest in all tests, including tensile, impact, roughness, torsion, compression, and hardness tests. The two most important contributing factors for evaluating the mechanical qualities of PA-12 at a high-grade level are the laser's 60-watt output and the layer's 0.06 mm thickness. In addition, with a layer thickness of 0.06 mm and a laser power of 60 watts, the dimensional accuracy test revealed 100% pure material for the X, and Y, demonstrating high accuracy in this study. Dimensional accuracy of this research 0.14 mm on the X-axis and 0.11 mm on the Y-axis were all result within the acceptable ±0.1% tolerance limits, indicating that the selected material composition and process parameters significantly enhanced dimensional accuracy beyond the manufacturer's standards. The Hence, this study has proven that recognising how process parameters affect accuracy is essential to achieving high accuracy in the production of 3D printed objects.